Total pharyngolaryngectomy in the elderly: The impact of age on postoperative complications and oncologic and functional outcomes. (December 2018) - Milliet, Florent; Gal, Jocelyn; Chamorey, Emmanuel; Dassonville, Olivier; Poissonnet, Gilles; Peyrade, Frédéric; Benezery, Karen; Hechema, Raphaël; Sudaka, Anne; Sanchez-Luini, Marine; Demard, François; Santini, José; et al.
Abstract: Objectives: To evaluate the clinical outcomes of total pharyngolaryngectomy (TPL) in the elderly and to analyze the impact of age on postoperative complications and oncologic and functional outcomes. Methods: We conducted a retrospective review of the medical records of all patients who underwent TPL for a laryngeal or hypopharyngeal squamous cell carcinoma, between 2000 and 2015. The impact of advanced age (>70 years) on clinical outcomes was assessed in univariate and multivariate analyses. Results: A total of 245 patients (mean age = 66.4 years) were enrolled in this study including 91 (37%) patients aged over 70 years. In patients aged over 70 years, local and general complication rates were 36% and 10%, respectively. Five-year overall, cause-specific and recurrence-free survival rates were 36%, 52% and 31%, respectively. Satisfactory swallowing (swallowing score ≥ 1; i.e. no enteral feeding) and speech (speech score ≥ 1; i.e. intelligible speech) functions were recovered by 94% and 70% of elderly patients. In multivariate analysis, older age had no significant impact on postoperative complications, oncologic outcomes and swallowing function. Compared to younger patients, elderly patients achieved significantly lower speech scores (p = 0.05). Conclusion: TPL is associated with favorable clinical outcomes in patients aged over 70 years and can therefore be considered a reliable therapeutic option. However, compared to younger patients, a lower level of recovery regarding speech function is expected in the elderly, and particular attention should be paid to the postoperative speech rehabilitation program in this population of patients. Highlights: Total pharyngolaryngectomy is associated with favorable clinical outcomes in the elderly. Older age has no significant impact on postoperative complications. Older age has no significant impact on oncologic outcomes and swallowing function. Older age was associated with poorer recovery regarding speech function.